McJingles: Om musik i tv-reklamer for McDonald’s-kampagnen i’m lovin’ it - Graakjær, Nicolai J. (Academic Quarter | Akademisk kvarter, 2011)
Nicolai Jørgensgaard Graakjær’s contribution, McJingles - On the use of music in the McDonald’s-campaign ’i’m lovin’ it’, is a stylistic and linguistic analysis of a slogan in an advertising campaign from McDonald’s. McDonald’s is one of the most prominent symbols of global culture and as such has been the focus of discussions about the homogenization of culture at a global level. Based on its analysis of the slogan’s musical minimization and variation Graakjær argues that McDonald’s does not only adapt itself to a time when the audience are saturated with advertising, but the burger chain, even though it strives for global standards, can still make cultural considerations and be adapted to local conditions. Here we see a different perspective linking well with the considerations that Karina M. Smed makes about the relationship between the global and the local based on tourism discourses.